1987
DOI: 10.1136/pgmj.63.739.363
|View full text |Cite
|
Sign up to set email alerts
|

Hemlock water dropwort poisoning

Abstract: Summary:Severe plant poisoning is relatively uncommon in adults. We report two adults who ingested hemlock water dropwort roots, having mistaken them for wild parsnip. One developed prolonged convulsions, severe metabolic acidosis and respiratory distress requiring mechanical ventilation. The toxin -oenanthotoxin -was detected in the gastric aspirate and measured by high performance liquid chromatography.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 5 publications
0
8
0
Order By: Relevance
“…The potent inhibition of GABAergic currents, known to play a crucial role in the inhibition in the adult CNS, would be an adequate explanation of the epileptogenic activity of OETX in the CNS (Chauvel et al. , 1978; Louvel and Heinemann, 1980; 1983; Ball et al. , 1987).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The potent inhibition of GABAergic currents, known to play a crucial role in the inhibition in the adult CNS, would be an adequate explanation of the epileptogenic activity of OETX in the CNS (Chauvel et al. , 1978; Louvel and Heinemann, 1980; 1983; Ball et al. , 1987).…”
Section: Discussionmentioning
confidence: 99%
“…It seems that the most prominent action of OETX on the CNS is induction of epileptic‐like activity (see also Chauvel et al. , 1978; Louvel and Heinemann, 1980; 1983; Ball et al. , 1987).…”
Section: Introductionmentioning
confidence: 99%
“…Roots from C. maculata and O. crocata retain their toxicity long after harvesting and/or drying [25,26]. Although cicutoxin and oenanthotoxin are relatively unstable compounds on exposure to air, light, and heat, poisonings after ingestion of dried and/or cooked roots of both O. crocata and C. maculata have been reported [3,4,27,28]. Pharmacological studies by Grundy and Howarth have demonstrated marked toxicity with dried and powdered tubers of O. crocata [29].…”
Section: Biochemistry Of Active Compoundsmentioning
confidence: 99%
“…Other reported neurological symptoms include amnesia [2,12,26], parathesias [27], neuropsychological abnormalities [6], and hallucinations [12,44]. Electroencephalograms show diffuse abnormalities that may be persistent [6,12,13,26,27]. Coagulopathy has been reported on multiple occasions [9,26].…”
Section: Clinical Presentationmentioning
confidence: 99%
See 1 more Smart Citation